2015
DOI: 10.1007/s00705-015-2517-9
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of scallop shell powders and slaked lime for inactivating avian influenza virus under harsh conditions

Abstract: The efficacy and stability of scallop shell powder (SSP) were investigated, in terms of its capacity to inactivate avian influenza virus (AIV), and compared with slaked lime (SL). An environmental simulation was conducted by emulating sunlight and wet-dry conditions. The powders were collected at consecutive 2-week intervals under sunlight and upon every resuspension. These materials were tested by mixing them with AIV and incubating the mixture for 3 min or 20 h, followed by AIV titration. At the same time, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 35 publications
0
26
0
Order By: Relevance
“…In harsh conditions, it is reported that slaked lime maintained its virucidal efficacy (RF>3) under sunlight for 3 weeks and that it showed high efficacy (RF>3) under wet and dry conditions for 3 times resuspension when the samples were evaluated using LPAIV H7N1 for 3 min [ 21 ]. In addition, it is suggested that after rain, slaked lime became hardened and it was difficult to take samples from the surface of the lime [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In harsh conditions, it is reported that slaked lime maintained its virucidal efficacy (RF>3) under sunlight for 3 weeks and that it showed high efficacy (RF>3) under wet and dry conditions for 3 times resuspension when the samples were evaluated using LPAIV H7N1 for 3 min [ 21 ]. In addition, it is suggested that after rain, slaked lime became hardened and it was difficult to take samples from the surface of the lime [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…RF=log 10 (amount of untreated intact pathogens/m l ) −log 10 (amount of treated pathogen with Egg-CaO/m l ). Inactivation was considered to be satisfied when RF was ≥3 [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…In the above equation, tpc is bacterial titer from an untreated sample in log 10 CFU/m l , whereas ta is the titer of recovered bacteria from treated samples. The inactivation rate was acceptable when the RF was greater than or equal to 3 [ 13 , 27 , 42 , 43 ].…”
Section: Methodsmentioning
confidence: 99%
“…There have been several trials to explain alternative materials for biosecurity enhancement, which do not interfere, even with contaminated organic materials. Several researchers have shown alkaline agents can inactivate bacteria, even in the presence of organic materials, such as bioceramic powder [26], slaked lime, scallop shell powder [28], calcinated egg shell [14], calcium hydroxide [20] and fresh charcoal ash [19]. However, several acidic agents, such as potassium monopersulfate, can inactivate both bacteria and viruses, even in the presence of organic material [22,23].…”
mentioning
confidence: 99%